Eucalyptus sp. seedling response to potassium fertilization and soil water. - Teixeira, Paulo César; Gonçalves, José Leonardo Moraes; Arthur Junior, José Carlos; Dezordi, Cleci (Ciência Florestal, 2008)
<!--[if gte mso 9]> Normal 0 21 MicrosoftInternetExplorer4 <![endif]--><!--[if !mso]> <mce:style><! st1\:*{behavior:url(#ieooui) } --> <!--[endif] --> <!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Tabela normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman";} --> <!--[endif] --> A considerable portion of Brazil‘s commercial eucalypt plantations is located in areas subjected to periods of water deficit and grown in soils with low natural fertility, particularly poor in potassium. Potassium is influential in controlling water relations of plants. The objective of this study was to verify the influence of potassium fertilization and soil water potential (Ψw) on the dry matter production and on water relations of eucalypt seedlings grown under greenhouse conditions. The experimental units were arranged in 4x4x2 randomized blocks factorial design, as follow: four species of Eucalyptus (Eucalyptus grandis, Eucalyptus urophylla, Eucalyptus camaldulensis and hybrid Eucalyptus grandis x Eucalyptus urophylla), four dosages of K (0, 50, 100 and 200 mg dm-3) and two soil water potentials (-0.01MPa and -0.1 MPa). Plastic containers with 15 cm diameter and 18 cm height, with Styrofoam base, containing 3.0 dm3 of soil and two plants per container were used. Soil water potential was kept at -0.01MPa for 40 days after seeding. Afterward, the experimental units were divided into two groups: in one group the potential was kept at -0.01MPa, and in the other one, at -0.10 MPa. Soil water potential was controlled gravimetrically twice a day with water replacement until the desired potential was reestablished. A week before harvesting, the leaf water potential (Ψ), the photosynthetic rate (A), the stomatal conductance (gs) and the transpiration rate were evaluated. The last week before harvesting, the mass of the containers was recorded daily before watering to determine the consumption of water by the plants. After harvesting, total dry matter and leaf area were evaluated. The data were submitted to analysis of variance, to Tukey's tests and regression analyses. The application of K influenced A, gs and the transpiration rate. Plants deficient in K showed lower A and higher gs and transpiration rates. There were no statistical differences in A, gs and transpiration rates in plants with and without water deficit. The addition of K reduced the consumption of water per unit of leaf area and, in general, plants submitted to water deficit presented a lower consumption of water.